2021
DOI: 10.1111/1541-4337.12755
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the dairy industry—Advances and opportunities

Abstract: The past two decades have witnessed a global surge in the application of probiotics as functional ingredients in food, animal feed, and pharmaceutical products. Among food industries, the dairy industry is the largest sector where probiotics are employed in a number of dairy products including sour/fermented milk, yogurt, cheese, butter/cream, ice cream, and infant formula. These probiotics are either used as starter culture alone or in combination with traditional starters, or incorporated into dairy products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 470 publications
(296 reference statements)
0
48
0
Order By: Relevance
“…Although other microorganisms are used in fermented dairy products, LAB has a greater place. The main dairy products in which LAB are used fermented milk, yogurt, infant formula, cheese, butter and cream, and ice cream [ 25 , 26 ]. In general, dairy products are considered primary dietary sources for LABs as probiotics which can be found naturally or added afterwards [ 27 ].…”
Section: Importance Of Labs In Dairy Foods In Terms Of Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Although other microorganisms are used in fermented dairy products, LAB has a greater place. The main dairy products in which LAB are used fermented milk, yogurt, infant formula, cheese, butter and cream, and ice cream [ 25 , 26 ]. In general, dairy products are considered primary dietary sources for LABs as probiotics which can be found naturally or added afterwards [ 27 ].…”
Section: Importance Of Labs In Dairy Foods In Terms Of Healthmentioning
confidence: 99%
“…In general, dairy products are considered primary dietary sources for LABs as probiotics which can be found naturally or added afterwards [ 27 ]. Although there is no certain cell count level that can guarantee the health effects of the probiotic strain in a food product, at least 10 6 –10 8 cfu/g is reported as a sufficient amount to benefit from the beneficial effects of probiotics [ 25 ]. This clearly shows that the presence of a culture that can show probiotic potentials does not guarantee that the product will be probiotic.…”
Section: Importance Of Labs In Dairy Foods In Terms Of Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, probiotics are most commonly used in plantbased butters such as peanut butter and butters from coconut, flaxseed, and sunflower oils. Although, recent studies have suggested the utilisation of probiotic bacteria (Bifidobacterium bifidum, Lactobacillus acidophilus, and L. maltaramicus) in butter elaborated from milk [76,77]. Conversely, probiotics strains usually isolated from commercially available fresh butter are not present in raw buffalo milk.…”
Section: Butter and Gheementioning
confidence: 99%
“…Conversely, probiotics strains usually isolated from commercially available fresh butter are not present in raw buffalo milk. On the other hand, probiotic microorganisms of buffalo milk L. delbrueckii and S. thermophilus were recently isolated from homemade butter and reported as starter cultures to butter fermentation processing [77]. To obtain the beneficial effects of butter as a functional food is recommend its consumption level at 25 g per day [76].…”
Section: Butter and Gheementioning
confidence: 99%